Toleransi Tanaman Sawi Hijau (Brassica juncea L.) Terhadap Cekaman Salinitas Garam NaCl - Irwan Lovadi, Eti Dwi Asih, Mukarlina (Jurnal Protobiont, 2015)
High levels of salt in the soil may cause the disruption of plant growth, especially the crops. Mustard greens (Brassica juncea L.) as the main vegetable commodity in West Kalimantan, is grown on soil with normally salinity level. The purpose of this research was to determine the growth response of mustard greens (B. juncea) against the exposure to the NaCl. The research was carried out from August to Oktober 2014. Research was carried out using the Completely Randomized Design (CRD), consisting of six treatment concentrations of NaCl i.e., 0 ppm, 2,000ppm; 4,000 ppm; 6,000 ppm; 8,000 ppm; 10,000 ppm respectively. The results showed real effects of the treatment onthe leaf area, length of the root, wet and dry weight, but had no real effect on the parameter of the number of chlorophyll. The whole treatment began to to affect the growth of mustard greens on the concentration of 4,000 ppm of NaCl. The range of tolerance of mustard green toward NaCl salt concentration was between 2,000 ppm – 10,000 ppm of NaCl.